(untitled) (Research, Society and Development, 2024)
The present study aims to investigate the effects of functional training on balance and the proprioceptive system in individuals with visual impairment. It is essential to highlight that people with visual impairment face specific difficulties and various challenges, especially in quality of life, given that their visual perception of the environment is greatly reduced. This limitation compromises the ability to carry out daily activities autonomously, directly impacting your quality of life. In this context, functional training emerges as a promising alternative to improve balance and the proprioceptive system in individuals with visual impairment, thus promoting a better quality of life. The methodology in this study is an integrative bibliographic review, based on theoretical studies related to the topic addressed. The research will use recognized databases, such as LILACS, VHL, CAPES, and SciELO, to compose the theoretical and methodological framework of the study. The study concluded that functional training improves balance, proprioception, and motor coordination in people with visual impairment, contributing to their autonomy and preventing falls.